Una metaheurística GRASP para integración en grafos - Dubinsky, Manuel (2017)
Given an edge-weighted graph, we analyze the problem of finding an orientation of its edges and a function on its nodes, such that for each oriented edge the consistent subtraction of the function on its incident vertices (ie.: head - tail), is the best approximation in a least square sense to the original edge-weighted function. We present a simple GRASP algorithm to find a “good” solution that is suitable for distributed execution.